The Toyota way : 14 management principles from the world's greatest manufacturer - Liker, Jeffrey K., ....- (New York (N.Y.) : McGraw-Hill, 2004)
Adopt these principles--known as the "Toyota Production System" or "Lean Production"--to improve the speed of your business processes, improve product and service quality, and cut costs, no matter what your industry. Drawing on his extensive research on Toyota, Dr. Liker shares his insights into the foundational principles at work in the Toyota culture. He explains how the Toyota Production System evolved as a new paradigm of manufacturing excellence, transforming businesses across industries. You'll learn how Toyota fosters employee involvement at all levels, discover the difference between traditional process improvement and Toyota's Lean improvement, and learn why companies often think they are Lean--but aren't. The fourteen management principles of the Toyota Way create the ideal environment for implementing Lean techniques and tools. Dr. Liker explains each key principle with detailed, examples from Toyota and other Lean companies on how to: Foster an atmosphere of continuous improvement
And improvement. You'll discover how the right combination of long-term philosophy, process, people, and problem solving can transform your organization into a Lean, learning enterprise--the Toyota Way.
And learning Create continuous process "flow" to unearth problems Satisfy customers (and eliminate waste at the same time) Grow your leaders rather than purchase them Get quality right the first time Grow together with your suppliers and partners for mutual benefit Dr. Liker shows the Toyota Way in action, then outlines how to apply the Toyota Way in your organization, with examples of how other companies have rebuilt their culture to create a Lean, learning enterprise. The Toyota Way is an inspiring guide to taking the steps necessary to emulate Toyota's remarkable success. What can your business learn from Toyota? How to double or triple the speed of any business process How to build quality into workplace systems How to eliminate the huge costs of hidden waste How to turn every employee into a quality control inspector How to dramatically improve your products and services! With a market capitalization greater than the value of General Motors, Ford, and Chrysler combined, Toyota is also, (by
At the University of Michigan and cofounder and director of the Japan Technology Management Program at the University of Michigan. Back cover copy "This book will give you an understanding of what has made Toyota successful and some practical ideas that you can use to develop your own approach to business."--Gary Convis, Managing Office of Toyota Fewer man-hours. Less inventory. The highest quality cars with the fewest defects of any competing manufacturer. In factories around the globe, Toyota consistently raises the bar for manufacturing, product development, and process excellence. The result is an amazing business success story: steadily taking market share from price-cutting competitors, earning far more profit than any other automaker, and winning the praise of business leaders worldwide. The Toyota Way reveals the management principles behind Toyota's worldwide reputation for quality and reliability. Dr. Jeffrey Liker, a renowned authority on Toyota's Lean methods, explains how you can
Far), the world's most profitable automaker. Toyota's secret weapon is Lean production--the revolutionary approach to business processes that it invented in the 1950's and has spent decades perfecting. Today businesses around the world are implementing Toyota's radical system for speeding up processes, reducing waste, and improving quality. The Toyota Way, explain's Toyota's unique approach to Lean--the 14 management principles and philosophy that drive Toyota's quality and efficiency-obsessed culture. You'll gain valuable insights that can be applied to any organization and any business process, whether in services or manufacturing. Professor Jeffrey Liker has been studying Toyota for twenty years, and was given unprecedented access to Toyota executives, employees and factories, both in Japan and the United States, for this landmark work. The book is full of examples of the 14 fundamental principles at work in the Toyota culture, and how these principles create a culture of continuous learning
How to speed up business processes, improve quality, and cut costs in any industry In factories around the world, Toyota consistently makes the highest-quality cars with the fewest defects of any competing manufacturer, while using fewer man-hours, less on-hand inventory, and half the floor space of its competitors. The Toyota Way is the first book for a general audience that explains the management principles and business philosophy behind Toyota's worldwide reputation for quality and reliability. Complete with profiles of organizations that have successfully adopted Toyota's principles, this book shows managers in every industry how to improve business processes by: Eliminating wasted time and resources Building quality into workplace systems Finding low-cost but reliable alternatives to expensive new technology Producing in small quantities Turning every employee into a qualitycontrol inspector Biographical note Dr. Jeffrey K. Liker is a professor of industrial and operations engineering
Keywords: Corporate culture -- History; Corporate culture; Industrial management; Industrial productivity; Production management -- Case studies; Production management; Social Sciences and Humanities. Management studies, Business Administration, Organizational Science -- Production Chain Management